The El Niño–Southern Oscillation teleconnection to southern Africa in a changing climate - Jessica Steinkopf; Francois Engelbrecht (Environmental Research Letters, 2025)
Understanding how El Niño Southern Oscillation (ENSO) influences African rainfall is critical for water and food security planning. However, how this teleconnection may change in a warmer world remains unclear. Coupled Model Intercomparison Project Phase Six (CMIP6) models simulate the observed ENSO-rainfall teleconnection well, with southern Africa dry (wet) and East Africa wet (dry) during El Niño (La Niña) austral summers. This dipole pattern remains remarkably stable in a warmer world, with strong model agreement. This suggests that the global and southern African circulation responses to ENSO (the teleconnection) remain robust under warming. However, parts of eastern southern Africa, including the water-critical Integrated Vaal River System catchment, the ENSO signal weakens or even reverses in CMIP6 model projections. This likely reflects a general wetting of eastern escarpment regions, especially during El Niños, which may be linked to mesoscale and oceanic processes associated with relatively warm El Niño events under future climate conditions.